Analysis of drug interactions in patients with heart disease: An experience report (International Seven Journal of Multidisciplinary, 2023)
Cardiopathic patients routinely use multiple medications. This polypharmacy, although an important strategy for the control of comorbidities, can lead to numerous drug interactions, in addition to results of altered magnitude and specificity¹. These interactions can be beneficial and expected, increasing treatment effectiveness, but they can also be undesirable, causing the opposite effect to the desired one. DOI:https://doi.org/10.56238/isevmjv2n2-006